Cell adhesion molecules and hyaluronic acid as markers of inflammation, fibrosis and response to antiviral therapy in chronic hepatitis C patients - Esther Granot; Daniel Shouval; Yaffa Ashur (Hindawi Limited, 2001)
Objective: Cell adhesion molecules (intracellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1)) and hyaluronic acid, markers of inflammation and fibrosis were monitored in hepatitis C patients to determine whether changes in plasma levels, during antiviral treatment, can predict long-term response to therapy.